An anaerobic dynamic membrane bioreactor for enhancing sludge digestion: Impact of solids retention time on digestion efficacy. (June 2021) - Chen, Guang; Wu, Wei; Xu, Jun; Wang, Zhiwei
Graphical abstract: Highlights: Increase of SRT led to an enhanced performance of sludge digestion in AnDMBR. Sludge concentration of membrane tank reached 56.3 g/L under SRT 50 d. At SRT 50 d, biogas yield of 0.79 L/g VS and VS reduction rate of 55.9% was reached. Both acetoclastic and hydrogenotrophic methanogenesis were found under higher SRT. The utilization of organic matter and acetate was also enhanced at longer SRT. Abstract: An anaerobic dynamic membrane bioreactor (AnDMBR), which enabled the decoupling of hydraulic retention time (HRT) and solids retention time (SRT), was used for enhancing sludge digestion, with the associated mechanisms elucidated. With the increase of SRT, the biogas production and sludge reduction rate were both enhanced. The specific biogas production and volatile solids (VS) reduction rate were improved to 0.79 L/g VS and 55.9% under SRT 50 d, respectively. Microbial community analysis revealed that Chloroflexi, which is capable of degrading metabolites and dead cells, was enriched at longer SRT. Further analysis showed that both acetoclastic and hydrogenotrophic methanogenesis contributed to the enhanced biogas production under higher SRT compared to the dominance of acetoclastic methanogenesis under lower SRT. The enhanced utilization of organic matter and acetate at longer SRT further confirmed the mechanisms. The results highlighted the potential of AnDMBR for high-efficient sludge digestion.